A study on health security scheme of Ayesha Abed Foundation artisan (workers) of AARONG and its effectiveness - Intesher, Ayeman Mohammad (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.